A new strategy to improve ramie degumming based on removal of the xylan branched structure. Issue 7 (April 2022) - Wang, Huihui; Shu, Tong; Li, Pandeng; Bai, Yun; Xiang, Mengxiong; Yu, Tianyi; Wu, Ya; Yu, Longjiang
Ramie fiber is known as the "king of natural fibers, " and the key to its wide application is efficient and green manufacturing. Microbial degumming has gradually become a hot area of research due to its environmental protection and mild operating conditions. However, some gummy materials remain after microbial degumming. Xylan is the main component of residual gums; its acetylated branched chains create the space barrier that makes the removal of hemicellulose difficult during ramie degumming. An acetyl xylan esterase (AXE) was obtained from Bacillus pumilus and characterized to solve this problem. Its optimum temperature and pH were 35°C and 8.0, respectively, and it had good temperature and pH stability. These properties were consistent with the conditions of ramie degumming and they laid a foundation for the application of AXE in ramie degumming. Besides, an engineered strain with a high activity of AXE was constructed successfully on the basis of the wild-type degumming strain Pectobacterium carotovorum HG-49 and used for ramie degumming. The removal rate of hemicellulose and total gums by the engineered strain increased by 4.89% and 2.53%, respectively, compared with that of the wild-type strain. Moreover, the role of this AXE in ramie degumming was further proven by X-ray diffraction and scanning electron microscopy. This study showed that AXE played an important role in the removal of hemicellulose in the degumming process of ramie fibers, thus providing a promising degumming strategy for ramie and other bast fiber plants.